A preliminary study of the plasma concentrations of orally administered fluconazole in alpacas (Vicugna pacos). Issue 1 (24th June 2021) - Butkiewicz, Christine D.; Shubitz, Lisa F.; Nix, David E.
Abstract: Alpacas residing in the region endemic for Coccidioides spp. are susceptible to serious, disseminated coccidioidomycosis that may result in death. There is currently no oral antifungal dose recommendation for this species. We used a steady‐state study design to assess the pharmacokinetics of oral generic fluconazole in alpacas dosed q 24 h for 14 days. Cohorts of 2–3 animals received fluconazole from 6 to 15 mg/kg/day, and pharmacokinetic analysis was performed after each group of animals in order to make dose adjustments for the next group. The final three animals were used as confirmation of our dose recommendation. The median T max was 7 h, and the median C max was 1.25 µg/ml per mg/kg dose. The mean dose‐normalized 24‐h AUC was 41.7 µg h/ml per mg/kg dose (CV = 72%). Based on these results, we recommend alpacas receive a starting dose of oral fluconazole at 10–15 mg/kg/day based on the fluconazole AUC in humans (313–625 µg h/ml). Testing to ascertain putative therapeutic plasma concentrations and monitoring of serum transaminases should be performed.